(untitled) (Muara Nada: Jurnal Pendidikan Seni, 2026)
Nggo Damba is a traditional percussion instrument originating from Keo Tengah Subdistrict and commonly used in cultural ceremonies, including the Peo-making ceremony and as accompaniment to the Sara Fai dance in welcoming guests. However, studies on Nggo Damba remain limited due to the lack of public knowledge regarding its presentation and playing techniques. This study aims to examine: (1) the form of presentation of the Nggo Damba musical instrument in the Sara Fai dance and (2) its functions in the cultural life of the community. This research employed a qualitative approach with an ethnographic method. Data were collected through observation, interviews, and documentation and analyzed descriptively. The findings show that the presentation of Nggo Damba in the Sara Fai dance consists of three stages: the opening stage, marked by a procession carrying the statue of the Virgin Mary accompanied by Nggo Damba; the main stage, which involves the traditional welcoming ceremony with customary greetings (Bheasa); and the closing stage, in which guests are welcomed through the Sara Fai dance accompanied by Nggo Damba music. In addition, Nggo Damba serves several important functions in the community, namely as a means of communication, a medium in traditional ceremonies, an accompaniment for welcoming guests, a supporting element in wedding ceremonies, and a form of entertainment. These findings indicate that Nggo Damba holds both artistic and sociocultural significance in the traditions of Keo Tengah Subdistrict.